A process for preparing activated carbon using coconut shell as raw material
By adding specific metal ions and sodium hydroxide solutions to the preparation process of coconut shell activated carbon, more micropores and voids are formed, the problem of insufficient removal rate of existing activated carbon when treating COD in industrial wastewater is solved, and efficient COD removal effect is achieved.
Patent Information
- Application Number
- CN202211688842.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-27
AI Technical Summary
When existing activated carbon treats COD in industrial wastewater, the removal rate is insufficient, resulting in limited application.
The activated carbon preparation process using coconut shell as raw material is used, and the specific surface area of activated carbon is impregnated by adding ferrous nitrate, cerium nitrate and copper nitrate solutions, combined with the impregnation and reactivated effect of sodium hydroxide solution, to form more micropores and voids, increasing the specific surface area of activated carbon.
It significantly improves the efficiency of activated carbon to remove COD in wastewater, provides a higher adsorption point, and meets the needs of efficient COD removal in industrial wastewater.
Smart Images

Figure GDA0005202343770000061 
Figure GDA0005202343770000071 
Figure GDA0005202343770000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of activated carbon preparation, and in particular relates to a process for preparing activated carbon using coconut shell as a raw material. Background Art
[0002] At present, the main wastewater discharge pollution industries in my country include electricity, chemical industry and papermaking industries. They are typical major polluters, and the wastewater discharged is generally a variety of mixed wastewater, with large water volume, complex composition and poor biodegradability. In addition, the country's wastewater treatment standards are constantly improving, and there are also very strict requirements for the removal of COD in wastewater. The organic matter in the wastewater consumes oxygen in both the chemical oxidation process and the biological oxidation process. The more organic matter in the wastewater, the more oxygen is consumed. The two are in a positive proportional relationship. COD can comprehensively reflect the number of all organic matter in the water. Therefore, it is widely used in water quality detection and analysis, becoming an important indicator for water quality monitoring and an important basis for environmental monitoring of water bodies. Therefore, how to remove COD in water has become the main task of today's scientific researchers.
[0003] Recently, activated carbon adsorption is one of the methods of sewage treatment, which can remove pollutants that are difficult to remove by general biochemical treatment and physicochemical treatment units. The range of adsorbents is very wide. It can not only deodorize, decolorize, and remove trace elements, but also adsorb many types of organic matter, such as: high molecular hydrocarbons, halogenated hydrocarbons, chlorinated aromatic hydrocarbons, phenols, benzene, and pesticides. Activated carbon adsorption technology was previously used in the water supply industry and was rarely used in the treatment of large-scale industrial wastewater. Because the COD concentration of industrial wastewater is high, the saturation cycle of activated carbon is short, and saturated carbon must be regenerated on-site, otherwise the operating cost is very high and it loses its use value. Nowadays, the industrial production of activated carbon regeneration has matured, but the use of activated carbon for COD removal in large-scale wastewater is still rare and the removal rate of activated carbon is far from enough to meet the demand. This factor limits the application of activated carbon adsorption technology in industrial wastewater. Therefore, it is of great significance to provide an activated carbon with a high COD removal rate. Summary of the invention
[0004] The purpose of the present invention is to provide an activated carbon with a high COD removal rate. To this end, the present invention provides an activated carbon preparation process using coconut shell as a raw material, wherein an appropriate amount of ferric nitrate solution, cerium nitrate solution and copper nitrate solution are added for impregnation, and after the impregnation is completed, drying and roasting are performed, so that more iron ions, cerium ions and copper ions enter the coconut shell activated carbon, and a synergistic effect can be generated between iron, cerium and copper, so that metals are appropriately loaded on the coconut shell activated carbon, further increasing the formation of micropores and gaps in the activated carbon, increasing the inner surface, and being beneficial to enhancing the removal treatment effect of COD in wastewater; a sodium hydroxide solution of appropriate concentration and amount is added for impregnation and reactivation, thereby creating a large number of micropores, effectively increasing the specific surface area of the activated carbon, providing more adsorption sites, and significantly improving the removal effect of COD.
[0005] The technical problem to be solved by the present invention is: how to improve the removal efficiency of COD.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A process for preparing activated carbon using coconut shell as raw material, the activated carbon preparation process comprising the following steps:
[0008] (1) Pretreatment: grinding the coconut shell, sieving, washing with distilled water, and then washing with anhydrous ethanol, drying completely after washing to obtain coconut shell powder, which is used for standby; mixing the ferric nitrate solution, the cerium nitrate solution and the copper nitrate solution in proportion to obtain a mixed solution, which is used for standby;
[0009] (2) preparing a preliminary product: weighing the coconut shell powder obtained in step (1), controlling the heating rate, and carbonizing the coconut shell powder; cooling the coconut shell powder to room temperature after carbonization; adding a sodium hydroxide solution, controlling the temperature for impregnation, and maintaining the temperature; adding deionized water and stirring the solution; and controlling the temperature for activation under a nitrogen environment after stirring to obtain a preliminary product;
[0010] (3) Preparation of activated carbon: The preliminary product obtained in step (2) is washed until it is neutral and stable, dried after washing, and then added with the mixed solution obtained in step (1) for impregnation. After impregnation, the filtrate is filtered, and the filtrate is dried under controlled temperature. After drying, it is calcined. After calcination, it is cooled to room temperature to obtain activated carbon.
[0011] Furthermore, the sieving in step (1) is through a 10-25 mesh sieve, the distilled water washing times are 2-3 times, and the anhydrous ethanol washing times are 3-5 times.
[0012] Furthermore, the temperature for complete drying in step (1) is 100-105°C.
[0013] Furthermore, in step (1), the volume ratio of the ferric nitrate solution, the cerium nitrate solution and the copper nitrate solution is 0.4-1.2:0.6-2.1:2-3.2, the concentration of the ferric nitrate solution is 0.3 mol / L, the concentration of the cerium nitrate solution is 0.2 mol / L, and the concentration of the copper nitrate solution is 1 mol / L. A synergistic effect can be produced between the iron ions, the cerium ions and the copper ions, so that the metal is appropriately loaded on the activated carbon, further increasing the formation of micropores and voids in the activated carbon, increasing the inner surface, and being beneficial to enhancing the removal treatment effect of COD in the wastewater.
[0014] Furthermore, in step (2), the ratio of the coconut shell powder to the sodium hydroxide solution is 15-23 g: 145-220 mL, and the concentration of the sodium hydroxide solution is 1 mol / L. The activated carbon prepared at this concentration has a large specific surface area, which avoids the situation where the activation reaction is too intense due to excessive concentration, and some micropores collapse due to excessive expansion to form mesopores and macropores, thereby reducing the specific surface area.
[0015] Furthermore, in step (2), the heating rate is 30-35°C / min, and the carbonization is performed by heating to 480-510°C and carbonizing for 50-60 minutes.
[0016] Furthermore, in step (2), the temperature of the temperature-controlled immersion is 80-85°C, the immersion time is 22-24h, the amount of deionized water added is until it is stirred into a slurry, and the controlled rate temperature activation is to heat the temperature to 680-720°C at a heating rate of 30-35°C / min and activate for 1.5-2h.
[0017] Furthermore, the drying condition in step (3) is to completely dry in an oven at 100-105°C.
[0018] Furthermore, the mixed liquid added in step (3) is 3-5 times the weight of the initial product, and the immersion time is 12-14 hours.
[0019] Furthermore, the drying conditions in step (3) are to control the temperature in an oven at 100-110° C. and dry for 18-22 hours, and the calcination is to calcine in a muffle furnace at 350-450° C. for 3-4 hours.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention adds appropriate amounts of ferric nitrate solution, cerium nitrate solution and copper nitrate solution for impregnation, and then dries and roasts the coconut shell activated carbon after impregnation, so that more iron ions, cerium ions and copper ions enter the coconut shell activated carbon, and a synergistic effect is produced between iron, cerium and copper, so that the metal is appropriately loaded on the coconut shell activated carbon, further increasing the formation of micropores and voids in the activated carbon, increasing the inner surface, and being beneficial to enhancing the removal treatment effect of COD in wastewater.
[0022] (2) The present invention adds a sodium hydroxide solution of appropriate concentration and amount for immersion reactivation, which reacts with the oxygen-containing functional groups formed on the surface of the previous carbonization product, making the contact more comprehensive and the reaction more complete, thereby creating a large number of micropores, effectively increasing the specific surface area of the activated carbon, providing more adsorption sites, and significantly improving the COD removal effect. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] A process for preparing activated carbon using coconut shell as raw material, the activated carbon preparation process comprising the following steps:
[0026] (1) Pretreatment: grind the coconut shell, pass it through a 20-mesh sieve, wash it 3 times with distilled water, and then wash it 3 times with anhydrous ethanol. After washing, dry it completely at 100° C. to obtain coconut shell powder for standby use; mix a 0.3 mol / L ferric nitrate solution, a 0.2 mol / L cerium nitrate solution, and a 1 mol / L copper nitrate solution in a volume ratio of 0.4:2.1:2.6 to obtain a mixed solution for standby use;
[0027] (2) Preparing a preliminary product: Weigh 23 g of the coconut shell powder obtained in step (1), control the heating rate to be 33° C. / min, heat to 495° C. for carbonization for 50 min, cool to room temperature after carbonization, add 183 mL of 1 mol / L sodium hydroxide solution, control the temperature to 83° C. for immersion for 23 h, maintain the temperature after immersion, add deionized water and stir until it becomes a slurry, heat to 700° C. at a heating rate of 30° C. / min under a nitrogen environment for activation for 2 h, and obtain a preliminary product;
[0028] (3) Preparation of activated carbon: The preliminary product obtained in step (2) is washed with distilled water until it is neutral and stable. After washing, it is dried completely in an oven at 105°C. Then, the mixed solution obtained in step (1) with a weight that is 3 times the weight of the preliminary product is added and immersed for 13 hours. After immersion, the filtrate is filtered and dried at 100°C for 20 hours. After drying, it is calcined in a muffle furnace at 350°C for 4 hours. After calcination, it is cooled to room temperature to obtain activated carbon.
[0029] Example 2
[0030] A process for preparing activated carbon using coconut shell as raw material, the activated carbon preparation process comprising the following steps:
[0031] (1) Pretreatment: grind the coconut shell, pass it through a 20-mesh sieve, wash it twice with distilled water, and then wash it four times with anhydrous ethanol. After washing, dry it completely at 100° C. to obtain coconut shell powder for standby use; mix a 0.3 mol / L ferric nitrate solution, a 0.2 mol / L cerium nitrate solution, and a 1 mol / L copper nitrate solution in a volume ratio of 0.8:0.6:3.2 to obtain a mixed solution for standby use;
[0032] (2) Preparing a preliminary product: Weigh 23 g of the coconut shell powder obtained in step (1), control the heating rate to be 35° C. / min, heat to 480° C. for carbonization for 55 min, cool to room temperature after carbonization, add 220 mL of 1 mol / L sodium hydroxide solution, control the temperature to 80° C. for immersion for 22 h, maintain the temperature after immersion, add deionized water and stir until it becomes a slurry, heat to 680° C. for activation for 2 h at a heating rate of 35° C. / min under a nitrogen environment to obtain a preliminary product;
[0033] (3) Preparation of activated carbon: The preliminary product obtained in step (2) is washed with distilled water until it is neutral and stable. After washing, it is dried completely in an oven at 105°C. Then, the mixed solution obtained in step (1) with a weight of 4 times that of the preliminary product is added and immersed for 14 hours. After immersion, the mixture is filtered. The filtrate is dried at 110°C for 18 hours. After drying, it is calcined in a muffle furnace at 400°C for 4 hours. After calcination, it is cooled to room temperature to obtain activated carbon.
[0034] Example 3
[0035] A process for preparing activated carbon using coconut shell as raw material, the activated carbon preparation process comprising the following steps:
[0036] (1) Pretreatment: grind the coconut shell, pass it through a 20-mesh sieve, wash it 3 times with distilled water, and then wash it 5 times with anhydrous ethanol. After washing, dry it completely at 105° C. to obtain coconut shell powder for standby use; mix a 0.3 mol / L ferric nitrate solution, a 0.2 mol / L cerium nitrate solution, and a 1 mol / L copper nitrate solution in a volume ratio of 1.2:1.4:2 to obtain a mixed solution for standby use;
[0037] (2) Preparing a preliminary product: Weigh 19 g of the coconut shell powder obtained in step (1), control the heating rate to be 30° C. / min, heat to 510° C. and carbonize for 60 min, cool to room temperature after carbonization, add 145 mL of 1 mol / L sodium hydroxide solution, control the temperature to 85° C. and immerse for 24 h, maintain the temperature after immersion, add deionized water and stir until it becomes a slurry, heat to 720° C. at a heating rate of 33° C. / min in a nitrogen environment and activate for 1.5 h to obtain a preliminary product;
[0038] (3) Preparation of activated carbon: The preliminary product obtained in step (2) is washed with distilled water until it is neutral and stable. After washing, it is dried completely in an oven at 100°C. Then, the mixed solution obtained in step (1) with a weight of 5 times that of the preliminary product is added and immersed for 12 hours. After immersion, the filtrate is filtered and dried at 105°C for 22 hours. After drying, it is calcined in a muffle furnace at 450°C for 3 hours. After calcination, it is cooled to room temperature to obtain activated carbon.
[0039] Comparative Examples 1-6
[0040] Compared with Example 3, in Comparative Examples 1-6, the volume ratios of the ferric nitrate solution, cerium nitrate solution and copper nitrate solution in step (1) are as shown in Table 1, and the remaining preparation steps and parameters are the same.
[0041] Table 1
[0042]
[0043]
[0044] Comparative Example 7
[0045] Compared with Example 3, the concentration of the sodium hydroxide solution in step (2) in Comparative Example 7 is 2 mol / L, and the remaining preparation steps and parameters are the same.
[0046] Comparative Example 8
[0047] Compared with Example 3, 140 mL of 1 mol / L sodium hydroxide solution was added in step (2) of Comparative Example 7, and the remaining preparation steps and parameters were the same.
[0048] Comparative Example 9
[0049] Compared with Example 3, 225 mL of 1 mol / L sodium hydroxide solution was added in step (2) of Comparative Example 7, and the remaining preparation steps and parameters were the same.
[0050] Performance Testing
[0051] (1) COD removal rate: According to standard GB 11914-89, the COD removal rate of the activated carbon prepared in Examples 1-3 and Comparative Examples 1-9 was measured;
[0052]
[0053] In the formula: COD1——COD value of wastewater before treatment;
[0054] COD2——COD value of treated wastewater.
[0055] The results are shown in Table 2.
[0056] (2) Specific surface area: The specific surface area of the activated carbons prepared in Examples 1-3 and Comparative Examples 7-9 was tested using a fully automatic specific surface area and porosity analyzer of model WBL-830. The results are shown in Table 2.
[0057] Table 2
[0058]
[0059]
[0060] It can be seen from Table 2 that the activated carbon prepared by the present invention has excellent COD removal performance and a large specific surface area.
[0061] The present invention adds appropriate amounts of ferric nitrate solution, cerium nitrate solution and copper nitrate solution for impregnation, and after the impregnation is completed, drying and roasting are performed, so that more iron ions, cerium ions and copper ions enter the coconut shell activated carbon, and a synergistic effect can be generated between iron, cerium and copper, so that the metal is properly loaded on the coconut shell activated carbon, further increasing the formation of micropores and gaps in the activated carbon, increasing the inner surface, and being beneficial to enhancing the removal treatment effect of COD in wastewater;
[0062] The present invention adds a sodium hydroxide solution of appropriate concentration and amount for impregnation reactivation, reacts with the oxygen-containing functional groups formed on the surface of the carbonized product in the early stage, makes the contact more comprehensive, and the reaction becomes more and more sufficient, thereby forming a large number of micropores, effectively improving the specific surface area of the activated carbon, providing more adsorption sites, and being beneficial to the removal of COD; in detail, it can be seen from Comparative Example 7 that the activated carbon prepared by the sodium hydroxide solution with too high concentration has a small specific surface area, because the activation reaction is too intense due to the high concentration, some micropores will collapse due to excessive expansion to form mesopores and macropores, so that the specific surface area becomes smaller; it can be seen from Comparative Example 8 that too little sodium hydroxide solution makes the contact between the carbonized product and the sodium hydroxide solution insufficient, which is not conducive to the generation of micropores, and the specific surface area is naturally small, and it can be seen from Comparative Example 9 that although too much sodium hydroxide solution enables it to continuously form pores, it may also be accompanied by perforation phenomenon in which the pore structure is destroyed, resulting in a small specific surface area.
[0063] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0064] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A process for preparing activated carbon using coconut shell as raw material, characterized in that: The activated carbon preparation process comprises the following steps: (1) Pretreatment: grinding the coconut shell, sieving, washing with distilled water, and then washing with anhydrous ethanol, drying completely after washing to obtain coconut shell powder, which is used for standby; mixing the ferric nitrate solution, the cerium nitrate solution and the copper nitrate solution in proportion to obtain a mixed solution, which is used for standby; The volume ratio of the ferric nitrate solution, the cerium nitrate solution and the copper nitrate solution is 0.4-1.2:0.6-2.1:2-3.2, the concentration of the ferric nitrate solution is 0.3 mol / L, the concentration of the cerium nitrate solution is 0.2 mol / L, and the concentration of the copper nitrate solution is 1 mol / L; (2) Activation: Weigh the coconut shell powder obtained in step (1), add sodium hydroxide solution, control the temperature and impregnate, control the heating rate after impregnation, perform carbonization, and cool to room temperature after carbonization to obtain a preliminary product; (3) Preparation of activated carbon: The preliminary product obtained in step (2) is washed with distilled water until it is neutral and stable, dried after washing, and then impregnated with the mixed solution obtained in step (1). After impregnation, the filtrate is filtered, and the filtrate is dried under controlled temperature. After drying, it is calcined. After calcination, it is cooled to room temperature to obtain activated carbon.
2. The process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: The sieving in step (1) is through a 10-25 mesh sieve, the distilled water washing times are 2-3 times, and the anhydrous ethanol washing times are 3-5 times.
3. The process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: The temperature for complete drying in step (1) is 100-105°C.
4. The process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: The coconut shell powder and the sodium hydroxide solution in the step (2) have a dosage ratio of 15-23 g:145-220 mL, and the concentration of the sodium hydroxide solution is 1 mol / L.
5. The process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: The temperature of the temperature-controlled immersion in step (2) is 80-85° C. and the immersion time is 22-24 hours.
6. The process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: The heating rate in step (2) is 30-35°C / min, and the carbonization is heating to 480-510°C and carbonizing for 50-60 minutes.
7. The process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: The drying condition in step (3) is to completely dry in an oven at 100-105°C.
8. The process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: The mixed liquid added in step (3) is 3-5 times the weight of the initial product, and the immersion time is 12-14 hours.
9. The process for preparing activated carbon using coconut shell as raw material according to claim 1, characterized in that: The drying conditions in step (3) are to control the temperature in an oven at 100-110° C. and dry for 18-22 hours, and the calcination is to calcine in a muffle furnace at 350-450° C. for 3-4 hours.
Citation Information
Patent Citations
Wheel discs
GB520053A
Method for preparing loading functional oxide porous carbon
CN101780952A